Pengembangan instrumen evaluasi kinerja pada Perpustakaan Universitas Kristen Satya Wacana Salatiga - Anton Hermawan; Anggita Kristiasari; Fransiska N. Bhiju; Dona Manik (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. Performance evaluation is the process of evaluating the implementation of the tasks of organizational members, including libraries, in accordance with the performance standards using particular way including instruments. Instruments are needed to document the evaluation carried out by the organization. Therefore, libraries need to pay attention to developa performance evaluation instrument to plan their human resources. This research explains an overview of stages in developing performance evaluation instruments in an organization, particularly libraries. Research methods. The research used a descriptive qualitative approach by involving the existing performance evaluation dimensions. After that, the performance evaluation indicators were developed. Data analysis. The measurement of validity and reliability was valid when the correlation between items was >0.3 and when Cronbach alpha was > 0.6. The measurement of validity and reliability help to support the development of performance evaluation instruments. Results and Discussion. Of the 36 statements, only 27 items were valid and used in performance appraisal instruments. The items are arranged in a model of development of the performance evaluation instruments. Conclusion and recommendations. A good organization needs to pay attention to the right indicators in an assessment instrument. In its application, it is effective to use the 360 ​​degree method, where employees are evaluated by other staff to ensure the balance professional perspective.